Political Marketing in Post-Conflict Elections: The Case of Iraq. Issue 3 (2nd July 2020) - Harmes, Adam
Abstract : This article examines political marketing in post-conflict elections through an illustrative case study of post-Saddam Iraq. It does so through articles and media reports as well as interviews and participant-observation research conducted in Iraq during the 2014 national and provincial elections. The article argues that, despite having a number of the comparative and ethnic conflict country characteristics that work against a market-oriented approach, Iraqi political parties have become increasingly professionalized and, to a lesser extent, willing to change their product in response to market research. It further argues that the Iraqi case can contribute to broader debates in the political marketing literature over the definition of market orientation and over the comparative factors that can help or hinder the spread of political marketing techniques.